Selective and Genetic Constraints on Pneumococcal Serotype Switching - Croucher,NJ; Kagedan,L; Thompson,CM; Parkhill,J; Bentley,SD; Finkelstein,JA; Lipsitch,M; Hanage,WP (Plos Genetics, 2015)
Streptococcus pneumoniae isolates typically express one of over 90 immunologically distinguishablepolysaccharide capsules (serotypes), which can be classified into “serogroups”based on cross-reactivity with certain antibodies. Pneumococci can alter their serotypethrough recombinations affecting the capsule polysaccharide synthesis (cps) locus. Twentysuch “serotype switching” events were fully characterised using a collection of 616 wholegenome sequences from systematic surveys of pneumococcal carriage. Eleven of thesewere within-serogroup switches, representing a highly significant (p < 0.0001) enrichmentbased on the observed serotype distribution. Whereas the recombinations resulting in between-serogroupswitches all spanned the entire cps locus, some of those that caused within-serogroupswitches did not. However, higher rates of within-serogroup switching couldnot be fully explained by either more frequent, shorter recombinations, nor by genetic linkageto genes involved in β–lactam resistance. This suggested the observed pattern was aconsequence of selection for preserving serogroup. Phenotyping of strains constructed toexpress different serotypes in common genetic backgrounds was used to test whether genotypeswere physiologically adapted to particular serogroups. These data were consistentwith epistatic interactions between the cps locus and the rest of the genome that were specificto serotype, but not serogroup, meaning they were unlikely to account for the observeddistribution of capsule types. Exclusion of these genetic and physiological hypotheses suggestedfuture work should focus on alternative mechanisms, such as host immunity spanningmultiple serotypes within the same serogroup, which might explain the observedpattern.